Osteoatritis Lutut dengan Hipertensi Derajat 1 pada Pasien Lanjut Usia: Sebuah Laporan Kasus - Mentari Putri Maharani; Winda Trijayanthi Utama (CV. Jasa Sukses Abadi, 2026)
Osteoarthritis (OA) and hypertension are chronic degenerative diseases commonly found in older adults and share interrelated pathophysiological mechanisms that may exacerbate each other through vascular, inflammatory, and functional decline pathways. This case report aims to describe a comprehensive approach in a patient with knee OA and stage 1 hypertension. A 62-year-old woman presented with chronic left knee pain that worsened with activity, accompanied by morning stiffness lasting less than 30 minutes. The patient had a history of uncontrolled hypertension and obesity with a body mass index of 27.6 kg/m². The diagnosis of knee OA and stage 1 hypertension was established based on history taking, physical examination, and clinical investigations. Management was performed comprehensively using pharmacological therapy consisting of sodium diclofenac, omeprazole, and amlodipine, along with non-pharmacological interventions including patient education, lifestyle modification, weight control, increased physical activity, and dietary adjustment. Particular attention was given to NSAID use in patients with cardiometabolic risk factors due to the potential for increased blood pressure and cardiovascular risk, necessitating careful risk–benefit consideration and regular clinical monitoring. Follow-up evaluation demonstrated improvement in blood pressure and reduction in pain, leading to enhanced daily functional capacity. This case highlights the importance of a multidimensional approach in OA with comorbid hypertension, focusing not only on symptom control but also on cardiovascular risk stratification, analgesic safety, and sustained lifestyle interventions to improve therapeutic outcomes and patient quality of life.